PENGARUH GAYA HIDUP DAN PEMASARAN MEDIA SOSIAL TERHADAPA KEPUTUSAN MEMBELI PRODUK LOKAL (STUDI PADA MAHASISWA FEB UNSRAT MANADO) - Poluan, Jane Grace; Rondonuwu, Christy Natalia; Karuntu, Merlyn Mourah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
As market behavior and technology develop, lifestyle and social media marketing become important variables that greatly influence purchasing decisions about a product. Activities or habits, interests and opinions which are lifestyle indicators will determine whether consumers want to buy local products or not. On the other hand, current social media marketing which more often displays foreign products is a challenge for local products to gain a place in the hearts of consumers, especially young students, namely students. This phenomenon was raised by researchers to conduct research aimed at exploring the extent to which lifestyle and social media marketing influence decisions to buy local products among FEB UNSRAT Manado students. This research is quantitative research with multiple regression methods. The population is all FEB UNSRAT students, with the sample determined using the purposive sampling method. The research results found that lifestyle had a significant influence on the decision to buy local products, social media marketing had a significant influence on the decision to buy local products, and lifestyle and social media marketing together had an influence on the decision to buy local products among FEB UNSRAT students.